A motivação suficiente das decisões judiciais: limites e equilíbrio entre as garantias constitucionais e a administração da justiça - Pontes, Pétrick Joseph Janofsky Canonico (2019)
The problem of this dissertation is to define the elements that constitute a motivate decision and, therefore, its validity or nullity. In other words, defining limits and balance of a complete motivation (sufficient) of judicial decisions, considering constitutional guarantees, the rules of Code of Civil Procedure and, under pragmatics and utilitarianism, the problems of the administration of justice. The motivation of judicial decision received a special attention by the Code of Civil Procedure of 2015. More than listed as an essential element of the sentence, Article 489, Paragraph 1, Code of Civil Procedure, identifies hypotheses in which a basis will not be considerated justified. The interpretation of such rules allows, a contrario sensu, to identify the elements for a sufficient motivation of decisions